"WHEN REWARDS NO LONGER MOTIVATE" TESTING THE MODERATING ROLE OF ORGANIZATIONAL AGILITY IN BUILDING INNOVATIVE LECTURERS IN THE ERA OF INDONESIA INDEPENDENT CAMPUS - Winarna, Aris; Keni , Keni; Michelle , Michelle (International Journal of Application on Economics and Business, 2023)
Innovative work behavior is the key to the performance and existence of an organization. In the context of business organizations, organizational factors that are antecedents of innovative work behavior are far from stable. Therefore, it is still necessary to conduct further research with different organizations and respondents. This study will examine organizational factors in Indonesian universities, which consist of: 1) organizational climate for innovation, 2) reward, 3) organizational agility as moderating variables. By using purposive random sampling involving 265 lecturers from universities in the Jakarta area, Indonesia, the results indicate that only the organizational climate for innovation variable has a significant positive effect directly on the innovative work behavior of lecturers. Meanwhile, the reward variable only has a partial significant positive effect after being moderated by the organizational agility variable. This phenomenon is a novelty in this study that rewards, which are believed to be able to change behavior as mentioned in social exchange theory so far, have experienced a shift in perceptions from lecturer respondents, where rewards are no longer motivating without including agility factors in their management. Organizational agility is a new term that is gaining popularity in strategic management which is defined as an agility that reflects flexibility, speed, accuracy, efficiency and innovation. This study has theoretical contributions and practical implications for higher education management and provides discussion and recommendations for future research.